2022
DOI: 10.3904/kjim.2022.099
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of acute upper gastrointestinal bleeding according to the risk indicated by Glasgow-Blatchford risk score-computed tomography score in the emergency room

Abstract: Background/Aims: Acute upper gastrointestinal (UGI) bleeding is a significant emergency situation with a mortality rate of 2% to 10%. Therefore, initial risk stratification is important for proper management. We aimed to evaluate the role of contrast-enhanced multidetector computed tomography (MDCT) for risk stratification in patients with acute UGI bleeding in the emergency room (ER).Methods: This retrospective study included patients with UGI bleeding in the ER. Glasgow-Blatchford risk score-computed tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…[ 9 , 12 ] Various scoring systems, such as the ABC score, [ 13 , 14 ] MAP score, [ 15 ] and GBS, [ 16 ] have been developed to classify high-risk patients. [ 17 ] Several studies have shown that the GBS is more effective than other scoring systems in predicting the need for endoscopic interventions. [ 18 ] A multicenter study performed in several countries showed that the GBS outperformed the pre-endoscopic Rockall score and the AIMS65 score when applied to predicting the need for endoscopic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 , 12 ] Various scoring systems, such as the ABC score, [ 13 , 14 ] MAP score, [ 15 ] and GBS, [ 16 ] have been developed to classify high-risk patients. [ 17 ] Several studies have shown that the GBS is more effective than other scoring systems in predicting the need for endoscopic interventions. [ 18 ] A multicenter study performed in several countries showed that the GBS outperformed the pre-endoscopic Rockall score and the AIMS65 score when applied to predicting the need for endoscopic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…2 Despite advances in diagnosis and treatment in recent years, the mortality rate in gastrointestinal system bleeding varies between 2 and 15% and, there is no decrease in mortality rate. 1,3,4 In patients with UGIB, the threshold for transfusion varies depending on comorbid diseases such as cardiovascular disease and liver insufficiency. Current guidelines from both the American College of Gastroenterology (ACG) and the European Society of Gastrointestinal Endoscopy (ESGE) advocate a restrictive transfusion approach in patients with UGIB without cardiovascular disease, starting at a hemoglobin (Hb) threshold of 7 g/dL and targeting a post-transfusion Hb level between 7 and 9 g/dL.…”
Section: Introductionmentioning
confidence: 99%
“…Upper gastrointestinal bleeding (UGIB) constitutes 60% of bleedings, and according to their anatomical localization, gastrointestinal bleeding is divided into two groups as lower and upper 2 . Despite advances in diagnosis and treatment in recent years, the mortality rate in gastrointestinal system bleeding varies between 2 and 15% and, there is no decrease in mortality rate 1,3,4 …”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [ 5 ] were the first to combine the findings of multidetector computed tomography (MDCT) with the Glasgow Blatchford scoring system. As MDCT greatly contributes to the diagnosis of gastrointestinal bleeding, particularly variceal bleeding, the development of an upper gastrointestinal bleeding score reflecting MDCT findings would help clinicians determine treatment strategies for emergencies.…”
mentioning
confidence: 99%